Perineal massage as a physical therapeutic resource for the prevention of laceration in vaginal birth: literature review (Research, Society and Development, 2022)
Perineal trauma during childbirth can occur spontaneously as a laceration or intentionally as in an episiotomy, being a common event especially in the first childbirth. It can be explained by the decreased flexibility of the pelvic floor muscles, physiological and anatomical changes suffered by the pregnant woman. As a physiotherapeutic resource, perineal massage has as main objective to promote relaxation and flexibility of this musculature, preventing dysfunctions in the perineal region. Objective: The study aimed to discuss and evaluate perineal massage as a physiotherapeutic resource in the prevention of lacerations caused by vaginal delivery. Materials and methods: This is an integrative review carried out in PubMed, PEDro and Scielo databases, seeking current evidence on the effectiveness of perineal massage in prepartum to prevent damage to the perineal musculature. Results: The study showed that perineal massage plays an important role in the prevention of perineal trauma, pelvic floor disorders, in addition to providing a faster and less painful recovery for the parturient, preventing its adverse effects in the long term.